Da Ghaznī tārīkhī jughrāfiyah - Zalmay, Muḥammad Walī (Da Afghānistān da Dimokrātīk Jamhūrīyat da ʻUlūmo da Akādmī da Ijtimāʻi ʻUlūmo da Markaz Khparawanah, 1983)
On the geography and history of Ghazni, Afghanistan.